The Role of Sharia Economic Law in Advancing MSME Digitalization for SDGs in Indonesia: A Systematic Literature Review (SLR) - Meriyati; Masykuri Abdillah; Muhammad Maksum; Idrus Alkaf; Imamul Arifin; Muhammad Amir Salim; Hamzah Al-Haqqoni; Mustamiruddin (Profetika: Jurnal Studi Islam, 2025)
Objective: This study aims to analyze the influence of Sharia Economic Law on the digitalization of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, with a focus on how Sharia-based regulations can support the digital transformation of these enterprises in line with the Sustainable Development Goals (SDGs). Theoretical framework: The theoretical framework is grounded in the concept of Sharia economic law, which emphasizes ethical business practices, social justice, and economic inclusivity, all of which are integral to the achievement of SDGs. Literature review: A review of relevant literature reveals that Sharia-based regulations, such as support for Sharia-compliant QRIS and the rise of halal fintech, have significantly facilitated the adoption of digital technology by MSMEs. These initiatives are aligned with SDGs, particularly in fostering economic growth (SDG 8) and promoting innovation (SDG 9). Method: The research uses a Systematic Literature Review (SLR) methodology, involving the collection and analysis of the latest academic articles, books, and policy reports related to the subject. The main research questions address the role of Sharia economic law in advancing MSME digitalization, the political dynamics influencing these developments, and the challenges and opportunities that emerge from this transformation. Results: The findings indicate that while the digitalization of MSMEs is progressing, there is a need for stronger integration between Sharia regulations and national laws, as well as efforts to improve digital literacy among MSME owners and employees. Additionally, it is important to create incentives to support the adoption of Sharia-based digital technology. Implications: The study's implications include providing policy recommendations for harmonizing regulations and fostering an enabling environment for the digital transformation of MSMEs in Indonesia. Novelty: The novelty of this research lies in its focus on Sharia economic law as a driver of MSME digitalization in Indonesia, a topic that has not been extensively explored.